Leitura e escrita para alunos do 3º ano do ensino fundamental: avaliação de um procedimento de ensino de discriminações condicionais com uso de software - Rainatto, Renata (2012)
Public Brazilian s schools have not promoted basic and fundamental aspects for the individual s life, such as the acquisition of reading and writing, for example. Behaviorists have done several researches in reading and/or writing, more recently based on stimulus equivalence studies, and show promising results for its application in the educational context. As the reading and writing are fundamental tools for the individual in society and considering the increasing number of fifth grade students who, as shown in SARESP s evaluation, don t reach the basic skills of reading and writing, the present study proposed evaluate a procedure to teach conditional discriminations with the use of educational software to students of 3nd year of elementary school. The following conditions were proposed: initial evaluation of reading and writing repertoires; teaching of relations between dictated word writing word images, as well as dictated word and writing word and letras e sílabas (the words were with and without complexities); evaluation of the emergence of expressive reading and writing; evaluation of reading's and writing's generalization (of words and sentences); final evaluation of reading and writing. The results have shown that the teaching procedure produced increase of reading and writing repertoires, of words and sentences, and have indicated that the equivalence stimulus model can be applied in educational context to students who have not acquired these repertories